Purulent encephalitis in a sheep flock - Mustafa Ortatatlı; M.Kemal Çiftçi; Mehmet Tuzcu (Eurasian Journal of Veterinary Sciences)
In this article, the clinic-pathologic and pathologic findings of purulent encephalitis observed in an Ak-karaman flock in a local (arm were described. Grossly, the foci of abscess and necrosis up to 4-6 mm diameter were seen in medulla oblongata, pons and cerebral hemispheres, and histopathologic ally microabscesses and purulent meningoencephalitis were detected. It has been considered that these cases might be an outbreak of a listeriosis.